2003
DOI: 10.1071/ea01146
|View full text |Cite
|
Sign up to set email alerts
|

Release of sterile Queensland fruit fly, Bactrocera tryoni (Froggatt) (Diptera: Tephritidae), at Sydney, Australia

Abstract: Four releases of sterile Queensland fruit flies were used in Sydney to assess their flight and distribution characteristics. Flies were detected within 400 m of the release site but did not reach the 5 km trapping array. The distribution was more pronounced towards the north-east and it may have been linked with strong wind prevailing in that direction. CLIMEX was used to indicate that the distribution was not limited by adverse weather. The distribution tended to agree with the formula predicted by Meats (199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 0 publications
2
95
4
Order By: Relevance
“…This is particularly the case when the reflected wavelengths of the pigments under UV light are not easy to differentiate, such as orange and pink (Dominiak et al 2003). It has also been suggested (Dominiak et al 2000(Dominiak et al , 2003 that different colours may have an effect on emergence and mortality of fruit flies. Colours of fluorescent pigment powders within a particular series have different chemical compositions (Safety Datasheets, T-series, Swada, Cheshire, U.K.).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly the case when the reflected wavelengths of the pigments under UV light are not easy to differentiate, such as orange and pink (Dominiak et al 2003). It has also been suggested (Dominiak et al 2000(Dominiak et al , 2003 that different colours may have an effect on emergence and mortality of fruit flies. Colours of fluorescent pigment powders within a particular series have different chemical compositions (Safety Datasheets, T-series, Swada, Cheshire, U.K.).…”
Section: Introductionmentioning
confidence: 99%
“…Originally developed by Norris (1957), the use of fluorescent pigments has been improved by other researchers (Dominiak et al 2000. Marking of insects with fluorescent pigments provides a quick and affordable technique to mark a large number of insects (Weldon 2005;Weldon et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Insects were reared out in a growth room at WWAI at 26 ± 2 C, 65 ± 15% RH and a light:dark period of 14:10 with a simulated dawn and dusk as the lights ramped up and down at the beginning and end of the photophase until release. Two separate trials were conducted and depending on each consignment, individual pupae weighed on average for trial 1, 11.4 (release 1) and 11.0 (release 2) mg and for trial 2, 9.85e11.38 mg respectively, which is within the expected range produced by the FFPF (Dominiak et al, 2008). When tested in all trials, the majority of sterile flies were aged 2e3 days.…”
Section: Study Insectsmentioning
confidence: 84%
“…Unfortunately, temperature changes can happen when insects are transported from the rearing site to the release site. Even a short duration temperature shock has been known to affect the quality of sterile insects (Dominiak et al 2007;Dominiak et al 2014). Carpenter et al (2012) found that irradiated codling moths were more likely to be of lower quality than non-irradiated after handling during transport.…”
Section: Radiation Dosementioning
confidence: 99%